Decision-making capacity, distress and decisional conflicts of patients with advanced cancer at the time of consent: empirical findings and ethical implications - Sabine Sommerlatte; Theresa Schneider; Julia Haberstroh; Christian Heise; Nina Lambrecht; Patrick Michl; Johannes Porzelle; Sophie Rauschenberg; Anke Reinacher-Schick; Matthias Richter; Julia Roick; Henning Rosenau; et al. (Journal of Cancer Research and Clinical Oncology, 2026)
Abstract Purpose The ability of cancer patients to make informed decisions may be limited due to psychological and emotional stress. The aim of this study is to describe the decision-making capacity of patients with advanced cancer and explore possible associations with their psychological health and decisional conflict. Methods We conducted structured interviews with patients having advanced pulmonal, oesophageal or liver cancer before the start of therapy and evaluated the decision-making capacity with the MacArthur Competence Assessment Tool for Treatment (MacCAT-T), decisional conflict using the Decisional Conflict Scale (DCS) and psychological distress utilizing the Hospital Anxiety and Depression Scale (HADS). We also examined the data for correlations between the items. Result Fifty-six patients (55% male, mean age 61.14 years) participated in the study. The results of the MacCAT-T revealed low performance in the domains of understanding and reasoning. The arithmetic average of 7 for the HADS-A ( n = 48, cut-off = 7) and 5.81 for the HADS-D ( n = 48, cut-off = 5) indicate that the patients experienced clinically relevant anxiety and depression symptoms. Out of 45 patients who completed the DCS, 15 (33.3%) showed a decisional conflict (cut-off = 37.5). A significant positive correlation was observed between the HADS and the DCS (HADS-A: ρ = 0.564, p < .001, HADS-D: ρ = 0.511, p < .001). Conclusion MacCAT-T results suggest low performance in the understanding and reasoning domains among some patients with advanced cancer. Psychological support and structured guidance in decision-making may improve patients’ ability to make informed decisions.